TREATMENT OF VICTIMS WITH EXTENSIVE BURNS: A SEVERE CLINICAL CASE - Емельянова, Альбина Миннегаязовна; Стяжкина, Светлана Николаевна; Шепелева, Валерия Михайловна; Тугбаева, Ольга Геннадиевна (Medicine in Kuzbass, 2020)
Objective – to consider the clinical case of treating a patient with a large area (65 %) of burn wounds, especially, the dynamics of the therapy during hospitalization and the treatment outcome. Methods. A retrospective analysis of the medical history was carried out, according to the purpose of the study, patient K., 52 years old, hospitalized from 22.08.2019 to 08.11.2019 (78 days in bed) in the hospital of the burn department of the First Republican Clinical Hospital Izhevsk. Results. The severity of the condition is due to the depth and area of thermal injury, the development of a burn disease, the presence of inhalation injury. Adequate anti-shock therapy (removal from the state of burn shock on the 2nd day of hospitalization), adequate antibacterial therapy with control of discharge from burn wounds, symptomatic treatment (analgesia, infusion and transfusion, antihypertensive therapy, treatment of inhalation injury and related diseases and complications), timely and rational surgical interventions, such as, phased necrectomy and 3 autodermoplasty. Conclusions. An adequate, rational treatment of a patient with extensive burns was carried out, having a value of Frank index of 155 upon admission (poor prognosis). The patient’s treatment was multidisciplinary, as during the course of treatment, doctors of various specialties were involved: surgery-combustiologists, anesthesiologists, resuscitators, therapist, pulmonologist, endoscopists and functional diagnostics, rehabilitation doctor. Hospitalization outcome: the patient was discharged with the full restoration of damaged skin.